2022
DOI: 10.1093/her/cyac008
|View full text |Cite
|
Sign up to set email alerts
|

Researchers or practitioners’ opinion of the possibilities for creating virtual safe social spaces for violence prevention interventions for young people

Abstract: Intimate partner violence (IPV) is a global concern. Interventions designed to prevent IPV are often participatory in nature, implemented in face-to-face settings and seek to create ‘safe social spaces’. We however do not fully understand how safe social spaces can be created in online spaces. Our study sought to understand the possibility of creating safe social spaces online, supportive of participatory interventions, from the perspective of those developing and implementing IPV prevention interventions. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This paper describes the online co-development process with learners, which was guided by steps one to four of the 6SQuID process (Figure 1). Prior to the co-development, we undertook a needs assessment with 18 learners via in-depth interviews (Ndungu, Magnolia, et al, 2022), and in-depth interviews with 20 researchers and practitioners in the field of VAWG prevention (Ndungu, Ngcobo-Sithole, et al, 2022a, 2022b, to explore the acceptability and feasibility of delivering VAWG prevention interventions online. In this paper, we report on the co-development process (Objective 3shaded in grey in Figure 1).…”
Section: Research Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper describes the online co-development process with learners, which was guided by steps one to four of the 6SQuID process (Figure 1). Prior to the co-development, we undertook a needs assessment with 18 learners via in-depth interviews (Ndungu, Magnolia, et al, 2022), and in-depth interviews with 20 researchers and practitioners in the field of VAWG prevention (Ndungu, Ngcobo-Sithole, et al, 2022a, 2022b, to explore the acceptability and feasibility of delivering VAWG prevention interventions online. In this paper, we report on the co-development process (Objective 3shaded in grey in Figure 1).…”
Section: Research Frameworkmentioning
confidence: 99%
“…sufficient to promote open discussions on sensitive topics (Ndungu, Ngcobo-Sithole, et al, 2022b;Sipes et al, 2022;Taddei & Contena, 2013). The ease learners found in building rapport could have been for a few reasons.…”
Section: Strengths and Limitations Of The Processmentioning
confidence: 99%
“…However, there are potential risks associated with online environments, including feelings of judgment and bullying (Denton et al, 2020; Price et al, 2017; Teaford et al, 2019). Ndungu et al (2022) reported it is much easier to bully someone in a chat space rather than face to face and raised concerns about how privacy and confidentiality would affect the ability to build relationships online. Patients' privacy could be compromised by sharing devices which is amplified by the ability to record sessions in an online group, something that is less likely to occur in person (Ndungu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Ndungu et al (2022) reported it is much easier to bully someone in a chat space rather than face to face and raised concerns about how privacy and confidentiality would affect the ability to build relationships online. Patients' privacy could be compromised by sharing devices which is amplified by the ability to record sessions in an online group, something that is less likely to occur in person (Ndungu et al, 2022). There can be barriers to psychological safety in online spaces such as how virtual interfaces interfere with presentation and recognition of non-verbal cues, body language, facial expressions, and eye contact (Dale-Tam, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation